A longitudinal study assessing depression in hepatitis C: Does gender play a role in the new-onset depression during interferon-alpha treatment?. Issue 2 (7th February 2019) - Fialho, Renata; Pereira, Marco; Gilleece, Yvonne; Rusted, Jennifer; Whale, Richard
ABSTRACT: In this prospective study conducted from October 2013 to June 2015 in Brighton, England, we examined differences between men and women in new-onset major depressive disorder (MDD) during interferon-alpha-based (IFN-α) therapy for hepatitis C virus (HCV). We included 155 HCV-infected patients (47 women), eligible to receive HCV therapy, including direct-acting antivirals. The Semi-Structured Clinical Interview was used to assess MDD. Severity of depressive symptoms was assessed using the Hamilton Depression Rating Scale. Patients were assessed at baseline, during treatment and 6 months after treatment completion. A significant increase in depressive symptoms was observed in the total sample from baseline to week 4, and a significant decrease was observed from end of treatment (week 24) to the sustained virological response (SVR) end point at 6 months posttreatment. Women were more likely to have a MDD at week 24. In both men and women, neurovegetative and mood-cognitive syndromes increased significantly at the early stage of treatment but remitted by the end of HCV therapy. Proportions with SVR were similar among females and males (91.5 percent vs. 87 percent). Under an inflammatory condition, boosted by interferon-based treatments, these results suggest that female gender is not associated with increased vulnerability for developing depression during IFN-α therapy.